Increasing VO2 Max through Circuit Training Training for Futsal Players at SMP Frater Makassar - Palamba, Fransiskus Hengky; Sahabuddin, Sahabuddin; Ishak, Muhammad; Hasmyati, Hasmyati; Hudain, Muh. Adnan (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2024)
The research objectives are to examine (1) whether there is VO2 Max before and after being given the circuit training intervention to futsal players at SMP Frater Makassar, (2) whether there is an influence of circuit training to increase VO2 Max for futsal players at SMP Frater Makassar. In this research, the researcher applied an experimental method, namely research that is always conducted to examine the influence of a treatment that has been given within a certain time. The research population was 21 members of futsal players at SMP Frater Makassar, so the researcher took a sample of 21 players with the criteria who were actively practising in the futsal team at SMP Frater Makassar. The results of the research reveal that there are differences in athletes' VO2 Max skills before being given circuit training intervention. The result of the descriptive analysis indicates that there is a significant increase in the VO2 Max value in futsal athletes at SMP Frater Makassar after implementing the circuit training program. Substantially different pretest and posttest scores indicate the effectiveness of the training program implemented. In the pretest, the athletes' VO2 Max value ranged from 23.2 to 38.2 points, with an average of 31.129 points and a standard deviation of 4.4029. After the circuit training program, the VO2 Max value increases to range between 28.7 to 48.0 points with an average of 38.976 points and a standard deviation of 6.4134. The increase in the average score from 31.129 to 38.976 points shows a significant increase in the athlete's aerobic capacity.